Membuka Wawasan Siswa dalam Perencanaan Orientasi Karir: Memasuki Dunia Kerja, Berwirausaha dan Studi Lanjut - Sriyani Mentari; Diana Tien Irafahmi (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
This Community Service Pogram aims to increase the insight of students of SMK Negeri 12 Malang regarding the working life, entrepeneur and continue to study. The method used in this activity is the provision of material to students. The result of this activity is an increase in the understanding of students of SMK Negeri 12 Malang about the working life, entrepeneur and continue study, this can be seen from the results of the questionnaire given to the participants of the activity. 83% of students understand more about the working life, entrepeneur and continue to study, 92% of students understand the positive and negative points if they choose to enter the workforce, entrepeneur or continue to study and 74% of students better understand how to choose a field of work or college major that matches their interests and abilities.